Menyelisik Budaya Kejawen dan Batasan Penerapannya dalam Kehidupan Islam - Sri Lestari; Choirunisa Mukaromah; Melan Deciani Dwi; Putti Nur Amaliah; Muhamad Parhan (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
Kejawen culture in Indonesia, especially in Javanese society, has a close relationship with Islam. These two beliefs run side by side, but in fact there are boundaries between the Kejawen culture and the Islamic religion. The purpose of this research is to find out how the Kejawen culture and the Islamic religion are, the difference between the two, and what are the boundaries in Islamic life. This study uses a literature review approach and qualitative methods to provide a comprehensive picture of the topic under study. Through a literature review, the authors can compile findings from various sources and provide in-depth argumentation of evaluations. The results of the study show that Islam and Kejawen culture are two different things but have always coexisted and have been inherent in Javanese society for a long time. In addition, Kejawen culture and Islamic religion have limitations in their application that can be known by the general public, namely the application of Islamic religious values by adapting local culture without eliminating Islamic principles.